Islamic Bank’s Financial Performance Indicators - Norazidah, Shamsudin; Fatimah, Mahmud; Safiynaz, Omar (Advances in Global Business Research, 2015)
Financial performance is pertinent in verifying the strength and survival of a company or business as the market player in the industry. However, there is an element which applied in the conventional bank but been prohibited to be applied and recognized by Islamic bank which is riba’ (interest) element. Conventional and Islamic banks have different practice in doing business which conventional bank would generate their main income from interest charged, but, Islamic bank is prohibited involve in riba’ (interest) practice. Unfortunately, financial performance of Islamic banks currently still be measured by conventional performance measurement which widely be measured by financial ratios. Since the recognition and approval of interest from these two types of bank is differ, hence, there is a need for different performance measurement indicators. In order to develop a unique indicator for financial performance, it should be refer to the objective of establishing the business. As for Islamic bank, supposedly the establishment of the institution is to fulfill the maslahah and shouldn’t be focused on profit-earnings as the priority.It is suggested Islamic banks should put maslahah and Maqasid al-Shari'ahas the main framework for Islamic financial performance measurement indicators. Hence, further study need to be done on reconstructing the pure framework of Islamic financial performance measurement.